INVENTARISASI KERAGAMAN PLASMA NUTFAH KACANG KOMAK (Lablab purpureus (L.) Sweet) DI KABUPATEN LOMBOK TENGAH PROVINSI NUSA TENGGARA BARAT - Ervina Titi Jayanti; Baiq Muli Harisanti (Bioscientist : Jurnal Ilmiah Biologi, 2013)
Peanut Komak (Lablab purpureus (L.) Sweet) is a member of Fabaceae commonly cultivated on the island of Lombok. So far, research on Komac Nuts in Indonesia is still very limited and only focused on biochemical content and its function as protein isolate. This study aims to inventory of germplasm diversity of Komac Nuts in terms of morphological characters in Central Lombok District. Collections of morphological samples (leaves, flowers, fruits, and seeds) were carried out using the exploratory method. The results of the study showed that 11 samples of Komac gene plasma were collected, based on morphological character of Komac nuts showed variation in stem color, flower color, pod characteristic (pod color, pod lip color and pod texture), seed characteristics (shape and color of seed, the presence of spots on the seed). The most commonly found germ plasm placma is that which has a white pod with a purple edge.